Gambaran Pengetahuan Ibu Hamil Tentang Tablet Fe Berdasarkan Karakteristik Ibu Hamil di Desa Kanaungan - Hajratul Azward (PPNI UNIMMAN, 2023)
The health problems facing the Indonesian nation today are the still high maternal and infant mortality rates, one of the causes of which is nutritional problems, namely anemia. The government has carried out a program to control anemia in pregnant women, namely by giving 90 Fe tablets to pregnant women, however regular consumption of Fe tablets is an important key which has not been implemented well, where South Sulawesi is the province with the lowest coverage with a percentage (1.7% ). The aim of the research is to determine the knowledge of pregnant women about Fe tablets based on the characteristics of pregnant women in Kanaungan Village using a descriptive method with a cross sectional approach. The population in this study of pregnant women who had their pregnancies checked at the Batara Siang Pangkep Regional Hospital which is domiciled in Kanaungan Village in 2023 numbered 226, with a sampling technique using Accidental Sampling, totaling 69 samples. From the research results, it can be concluded that most of the respondents were aged 20-35 years (88.4%), had junior high school education (44.9%), were employees/private sector (62.3%) and had less knowledge (43.5%).